Abdominal Hysterectomy: A New Approach for Conventional Procedure - Dutta, Dilip Kumar (Journal of clinical and diagnostic research, 2014)
The present comparative study helps in developing a new approach to conventional hysterectomy procedure so as prevent intra-operative and Post-operative complications during the procedure. Ligation of uterine and ovarian arteries was performed, prior to abdominal hysterectomy procedures, in Group A (n-1000) and conventional method of abdominal hysterectomy in Group B (n-450) from January 2000 to December 2009. It was a prospective study. In Group A it was noted that traumatic injury to (L) uterine vessel was present in 4 (0.4%) cases and (R) uterine vessel in 3 (0.3%) cases without any noticeable injury to the ovarian vessels, ureters or bladder as compared to in Group B where injury to (L) uterine was noted in 11 (2.4%) cases, ureters in 1 (0.1%) case, bladder in 6(1.5%) cases, hematoma in 10 (2.2%). Post-operative complications were found to be uneventful in Group A. The Present study concludes that ligation of uterine and ovarian arteries, prior to conventional abdominal hysterectomy procedures is found to be extremely safe procedure thereby reducing the risk of intra-operative and post- operative complications.